Cultura informacional voltada à inteligência competitiva organizacional no setor de calçados de São Paulo - Woida, Luana Maia [UNESP] (2008)
The footwear industry in the state of São paulo is one of the industries that more contribute to supply the footwear demand, both, in the country and abroad. Consequently, it is a representative industry for brazil, being so, it needs information and comunication and information technologies (ICTs), to work in the competitive environment mainly, regarding the foreign market and turning to exportation. This sector showed a need for achievement of a study that involves subjects such as the organizational competitive intelligence (OCI) and the information culture (IC), to establish the relation among people the information and the information and communication technologies in this context. The relevance os this research is relevanted, since it will be able to provide an IC concerning the model of the organizations that belong to the footwear industry in the state of São Paulo. From the analyses of data and information collected in the observed reality, it was possible to propose an IC model turned to the OCI process. The main objective of this culture, essential to the OCI process in companies of the footwear industry in the state of São Paulo. It’s presumed that there’s a relationship between the process and the cultural elements that must be investigated, focusing mainly in the information transfer and knowledge process. The methodological procedures were anchored in the qualitative approach, which approach refers to the descriptive-exploratory research, as well as to comparative approach. As data collecttion instrument were used: a questionnaire, with mixed questions, a script of the interview and an observation script. Aiming the qualitative analyses applied to the Bardin’s “Analyses Content”, in a way to attend the complexity in the approached subjects.